The Provision of E-Modules on Adolescent Mental Health Understanding - Nurul Devi Ardiani; Siti Mardiyah (International Journal of Public Health Excellence (IJPHE), 2023)
Mental health frequently receives inadequate attention and is often disregarded by individuals who tend to prioritize physical health over mental well-being. The occurrence of mental disorders in adolescents (aged 15-24 years) is associated with a depression rate of 6.2%. Severe depression tends to lead to self-harm and suicide. Approximately 80-90% of suicide cases can be attributed to depression and anxiety. A comprehensive understanding of adolescent mental health is essential for determining appropriate actions to make adolescents aware that mental health is equally essential. Preventing mental health issues in adolescents is crucial for avoiding further mental disorders or psychological problems. Prevention can be effectively achieved through health education for adolescents, enabling them to comprehend the significance of their mental health. E-modules provide an ideal medium for reaching adolescents, as they adapt conventional modules by incorporating information technology, making them more engaging and interactive. This enhances their appeal as an engaging and interactive learning resource. Digital modules (e-modules) enriched with audiovisual technology are expected to apprehend students' interests and create a conducive learning environment. The research objective was to investigate the effect of E-modules on adolescents' understanding of mental health. The study adopted a quantitative approach, using a quasi-experimental research design with a pre-posttest without control, conducted through intervention with a single group. The study was conducted at SMP 8 Surakarta and data were collected before and after the intervention. Data analysis employed the Wilcoxon test was used to obtain a significant result with a p-value of 0.01 (p < 0.05). Based on these findings, E-modules affected adolescents' mental health acquaintances.